Nonlinear Control Of Robot Manipulator Using Sliding Mode And Computed Torque Control Technique - Umar, Siti Nur Hanisah (2015)
The idea of a robot is created based on human and biological nature. The purpose of creating robots is to replace human work that is tiresome, repetitive, or dangerous task in industries or military application. The most extensively used is the manipulation robot system which can be found in manufacturing industries. This type of robot is an arm-link mechanism system, and the control objective is to manipulate material without direct contact by commanding the end-effector motion to achieve the desired operation. For this purpose, the study on the relation of joint-space and Cartesian-space, together with the control system, is essential. The objectives of this research are to study the linear Proportional, Integrator and Derivative (PID) control, nonlinear Computed Torque Control (CTC) and Sliding Mode Control (SMC), and the control algorithm was built using MATLAB Simulink block. The control algorithm of the PID, PIDCTC and SMCTC were implemented into the robot manipulator, where the controller parameters were determined within a prescribed range. The performance of the control system was tested for step response, position tracking and modelled estimation. An additional test for chattering reduction has been carried out for SMCTC with reaching control law. Based on the results, the performance of each of the controllers was compared. The PID control system shows a relatively good performance within the requirements of this study. Also, the PIDCTC produced better results than the PID controller, especially for position tracking. However, when the system were subjected to external disturbance, both controllers were unable to reject the disturbance. The SMCTC is robust towards external disturbance, and has shown the best performance. The implementation of reaching control law not only reduced the settling time, but was also able to eliminate the chattering phenomenon. The effectiveness of SMCTC has been shown by its implementation into a servomotor robot manipulator. Based on the results, the experimental performance has shown that both joints are able to reach the position as desired.